KORELASI SOFT SKILLS TERHADAP DURASI MASA STUDI ALUMNI PRODI PENDIDIKAN TEKNIK BANGUNAN FT UNP - Putri Erzha Ichsantiah; Drs. Iskandar G. Rani, M.Pd (Universitas Negeri Padang, 2019)
Abstract― These studies are motivated by the delay in the study of Building Engineering Education Alumni Study and the lack of student awareness of soft skills in the learning process on campus. Therefore, it is necessary to know whether there is a relationship between soft skills and the duration of the Alumni Study Program in Building Engineering Education FT UNP. This type of research is descriptive research. The study population was 113 Alumni Education Engineering Study Program alumni of the class of 2012, 2013 and 2014 who had completed their studies from September 2016 to September 2018. The sampling technique used was the Taroyamane formula. There are two data obtained in this study, namely primary and secondary data. Primary data is obtained through questionnaires distributed to respondents, while secondary data are all data obtained from the administration of Civil Engineering FT UNP. Data analysis techniques used are: 1) Descriptive data analysis, 2) Test requirements analysis consisting of normality test and linearity test, 3) hypothesis testing consisting of correlation test, significance tes and determinant coeficien test. The results showed that there was a relationship between soft skills and the duration of the study period. In this study, soft skills were found to contribute 10.11% to the duration of the study period. Keywords: Soft Skills, Duration of Study Period.